TERMS RELATED TO THE FIELD OF ARCHITECTURE AND CONSTRUCTION (Multidisciplinary Journal of Science and Technology, 2024)
In order to carry out research at the points of intersection of architecture and construction with language, it is necessary to clarify several concepts and paradigms related to this process. Regarding the definition of the term, there are a lot of opinions expressed in scientific sources. In almost all definitions, the term is described as a word or phrase expressing a special scientific and technical concept. In this article has shown the influence of word and term in national lexicon.